Impact of symptom severity in patients with diarrhoea-predominant irritable bowel syndrome (IBS-D): results from two separate surveys of HCPs and patients with IBS-D - Emmanuel, Anton (BMC Gastroenterol, 2020)
BACKGROUND: Management of diarrhoea-predominant irritable bowel syndrome (IBS-D) is generally based on patient-reported symptoms; however, limited information on symptom severity exists. The objective of the study was to assess the impact of IBS-D severity on patient burden and patient and healthcare professional attitudes towards IBS. METHODS: We conducted two web-based surveys of healthcare professionals and patients from Australia, Canada and Europe. We analysed patient characteristics and attitudes by IBS-D severity, which was assessed retrospectively using a composite of four variables: worst abdominal pain, IBS symptom frequency, Bristol Stool Form Scale and quality of life. RESULTS: Of 679 healthcare professional respondents, one-third routinely classified patients by severity. The patient survey was completed by 513 patients with mild (26%), moderate (33%) and severe (41%) IBS-D, classified using the composite scale. Age, sex and treatment satisfaction did not change with severity; however, 19% of patients classified with severe IBS-D agreed with the statement: ‘When my IBS is bad, I wish I was dead’ versus 4 and 7% of patients with mild and moderate IBS-D, respectively (p < 0.05). Significantly more patients classified with severe IBS-D reported medication use versus mild IBS-D. CONCLUSION: Compared with milder symptoms, severe IBS-D was associated with increased medication use and a negative perspective of IBS-D. This highlights the need for a validated severity scale to inform treatment decisions.